(untitled) - Markstein, Linda (Boston, MA, 1994)
The book provides text for those who want to develop their reading skills for academic, personal, or career purposes. The text is also appropriate for high school students. This book was designed for students of English as a second language and english as a foreign language in both academic and nonacademic sttings.
Keywords: English language,English language; Textbooks for foreign speakers.,Rhetoric